2015
DOI: 10.2460/javma.247.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative red blood cell transfusion requirement for various surgical procedures in dogs: 207 cases (2004–2013)

Abstract: Results indicated that dogs undergoing splenectomy and liver lobectomy may require RBC transfusion perioperatively. Veterinarians who perform these procedures should plan accordingly and have packed RBCs or whole blood donors readily available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…11,12 Evidence from studies conducted on animals undergoing thyroidectomy indicates poor survival rates among BT recipients. 13 Only around 0.11% of patients undergoing thyroidectomy require BT. 14 Due to this rarity, there is paucity of data on BT in thyroidectomy patients, and therefore, risk factors and outcomes of BT in this population remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Evidence from studies conducted on animals undergoing thyroidectomy indicates poor survival rates among BT recipients. 13 Only around 0.11% of patients undergoing thyroidectomy require BT. 14 Due to this rarity, there is paucity of data on BT in thyroidectomy patients, and therefore, risk factors and outcomes of BT in this population remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from studies conducted on animals undergoing thyroidectomy indicates poor survival rates among BT recipients 13 . Only around 0.11% of patients undergoing thyroidectomy require BT 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our study found that 36.3% (4/11) of dogs that received a blood product transfusion (two FFP, one WB and one pRBC) and 20% (1/5) of cats (pRBC) died, which may be consistent with the previous literature. Haley et al (2015) found blood product transfusion to be a negative prognostic indicator and Hanson et al (2017) showed that the mortality rate was significantly higher in dogs requiring a blood transfusion. Future large, multi-institutional prospective studies looking at transfusion types, indications, and outcomes in dogs and cats undergoing pancreatic surgery are necessary to help determine the true significance of transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…Haley et al . (2015) found blood product transfusion to be a negative prognostic indicator and Hanson et al . (2017) showed that the mortality rate was significantly higher in dogs requiring a blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…That is, as an adjunct to direct suction intraoperatively to maximize recovery. Haley et al found that dogs undergoing liver lobectomy and splenectomy are statistically more likely to require transfusion perioperatively 22 . In these situations, autotransfusion following cell salvage would be particularly valuable intraoperatively and would avoid the challenges of logistics and availability of allogeneic blood products.…”
Section: Discussionmentioning
confidence: 99%